2015
DOI: 10.1007/s11368-015-1239-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of emerging organic micropollutants onto fine sediments in a water supply dam reservoir, Poland

Abstract: Purpose Sorption studies of organic micropollutants to sediments are useful for predicting their fate and transport. They allow for a better understanding of the migration of contaminants through environmental media, the exposure of aquatic organisms to such chemical and their affect on human health. Materials and methods This study examined the sorption of carbamazepine, ketoprofen, diclofenac, bisphenol A and triclosan onto sediments sampled along a dam reservoir. The sediments differed in structure, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…In studies of pharmaceuticals adsorption in river sediment samples, it was shown that the sorption of carbamazepine and diclofenac was higher than for ibuprofen, namely KD for CBZ was in the range of 5.57-24.55 L kg −1 and KD for DIC was 4.04-33.01 L kg −1 [55]. Similar results were also obtained for soil samples collected from dam reservoirs, where KD of CBZ was 2.9-5.5 L kg -1 , and 4.8-5.5 L kg −1 for DIC [20], and in tropical soil samples CBZ was 0.83-3.38 L kg −1 [56].…”
Section: Study Of the Sorption Efficiency Of Selected Drugs On Soilsupporting
confidence: 75%
See 2 more Smart Citations
“…In studies of pharmaceuticals adsorption in river sediment samples, it was shown that the sorption of carbamazepine and diclofenac was higher than for ibuprofen, namely KD for CBZ was in the range of 5.57-24.55 L kg −1 and KD for DIC was 4.04-33.01 L kg −1 [55]. Similar results were also obtained for soil samples collected from dam reservoirs, where KD of CBZ was 2.9-5.5 L kg -1 , and 4.8-5.5 L kg −1 for DIC [20], and in tropical soil samples CBZ was 0.83-3.38 L kg −1 [56].…”
Section: Study Of the Sorption Efficiency Of Selected Drugs On Soilsupporting
confidence: 75%
“…Procedures to produce SUPRAS solvents compatible with chromatographic and electrophoretic techniques are currently being developing [20]. Very often, supramolecular solvent-based microextraction (SUPRAS microextraction) uses decanoic acid (DeA) with tetrahydrofuran (THF) as the amphiphilic compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acts primarily by selectively inhibiting cyclooxygenase (COX-1) (Knopp et al 2007 ) 318.13 0.6–0.8 experimental at the pH ≥ 10 (Ingram et al 2011 ) 1.26–2.18 and 0.39–1.56 thermophilic and mesophilic digested sludge (Carballa et al 2008 ) 0.68–0.74 sediments from Dobroczyn basin, Poland (Styszko 2016 ) 4–92 a ng/g river sediments, Túria River, Spain (Carmona et al 2014 ) 0.1–0.3 μg/g soil cores, Jerez de la Frontera and Guadalete alluvial aquifer, Spain (Corada-Fernández et al 2015 ) LOD—19 ng/g lettuce—dry weight (Calderón-Preciado et al 2013 ) Average 17.8 ng/g eggplant—dry weigh (Riemenschneider et al 2016 ) Ketoprofen A non-steroidal anti-inflammatory drug (NSAID) with anti-inflammatory, analgesic, and antipyretic activity. Drug acts by inhibiting both the constitutive (COX-1) and inducible (COX-2) types of cyclooxygenase (Thyss et al 1986 ) 254.28 3.12–3.16—model simulation (Tixier et al 2003 ) 0.66–1.07 foam-textured soil (Zhang et al 2017 ) 0.11–0.30 sediments from Dobroczyn basin, Poland (Styszko 2016 ) max. 97.35 ng/g natural, industrial, and agricultural soil, Cartagena-La Unión (Murcia), forest area of Monte de las Cenizas (Gutiérrez et al 2016 ) Data not available Chloramphenicol An antibiotic agent produced by Streptomyces venezuelae.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, new sorbents and approaches to SPE have been developed that improve the selectivity of existing commercial phases and lower the cost of analyte extraction. New sorbents for preconcentration of trace elements is a common subject, and some novel materials have been developed recently, such as molecularly imprinted polymers, carbon nanotubes, nanoparticles, biosorbents, and conducting polymers .…”
Section: Introductionmentioning
confidence: 99%